2001
DOI: 10.1148/radiology.218.3.r01mr44866
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Core-Needle Breast Biopsy: A Multi-institutional Prospective Trial

Abstract: Percutaneous stereotactic CNB is an accurate method to establish a histopathologic diagnosis of nonpalpable breast lesions. Accuracy increases when additional surgery is performed for lesions with anticipated sampling error or when CNB findings are discordant with mammographic findings. An understanding of the interrelationship among these parameters is necessary to properly assess results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 45 publications
5
50
0
1
Order By: Relevance
“…The high ratio of malignancies in the latter study was associated with the selection of patients from high-risk groups. Other studies have also led to similar results (Brenner et al, 2001;Ciatto et al, 2006). In our study, 71.6% of the lesions in the patients who had undergone SVC biopsies were benign, and 28.4% were malignant.…”
Section: Discussionsupporting
confidence: 66%
“…The high ratio of malignancies in the latter study was associated with the selection of patients from high-risk groups. Other studies have also led to similar results (Brenner et al, 2001;Ciatto et al, 2006). In our study, 71.6% of the lesions in the patients who had undergone SVC biopsies were benign, and 28.4% were malignant.…”
Section: Discussionsupporting
confidence: 66%
“…It has been demonstrated that SNCB has high sensitivity in the diagnosis of both malignant and benign conditions. 3,4,7,8,10 SNCB reduces the financial and personal cost of diagnosis, leads to a reduction in surgical biopsies, and increases the positive predictive value of surgical biopsy. 43,44 Morbidity is reduced, and cosmesis is better compared with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Previous studies have reported high rates of concordance between the histologic findings of core biopsy and surgical biopsy. An exception is atypical ductal hyperplasia (ADH), which is an unreliable core biopsy diagnosis that requires surgical biopsy, 1,8,10 -13 because low-grade ductal carcinoma in situ (DCIS) and ADH may be confused on core biopsy due to the small volume of tissue sampled.…”
mentioning
confidence: 99%
“…Stereotactic incisional core breast biopsy (SCBB) has been shown to be a useful method for investigating nonpalpable masses or suspicious calcifications that are detected on screening mammogram (1)(2)(3)(4)(5)(6). In many specialized centers, it has become the preferred method of tissue sampling for such lesions.…”
mentioning
confidence: 99%